Ground reaction forces during the golf swing using different golf clubs in female golfers - Hirano, T.; Kashiwagi, Y.; Inoue, Y.; Kihara, Y.; Shimatani, S.; Funato, K.; Ae, M. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate effects of different golf clubs on the ground reaction forces during the golf swing for females. Ten right-handed female varsity golfers voluntarily participated in this study. Using three different clubs, they hit the ball by their own swing in four conditions (full driver shot, controlled driver shot, 6-iron shot, and approach-wedge shot). Their motion was three-dimensionally captured which was performed with one foot on each force plate. There were no significant differences in the peak resultant forces between the golf clubs, but the peak resultant horizontal force differed between the golf clubs. The female golfers` resultant reaction force patterns were classified into three patterns, indicating that the golfers generated the reaction forces in their own ways, which would reflect the characteristics of their golf swing.